2017
DOI: 10.3168/jds.2016-11264
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Microbe-mediated aflatoxin decontamination of dairy products and feeds

Abstract: Aspergillus flavus, Aspergillus parasiticus, and Aspergillus nomius contaminate corn, sorghum, rice, peanuts, tree nuts, figs, ginger, nutmeg, and milk. They produce aflatoxins, especially aflatoxin B, which is classified as a Group 1 carcinogen by the International Agency for Research on Cancer. Many studies have focused on aflatoxin removal from food or feed, especially via microbe-mediated mechanisms-either adsorption or degradation. Of the lactic acid bacteria, Lactobacillus rhamnosus GG efficiently binds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 92 publications
0
45
0
2
Order By: Relevance
“…JFDS-2017-0976 Submitted 6/16/2017, Accepted 2/7/2018 Owing to the harmful impact of AFs on human health, it is necessary to prevent the formation of AFs, ensure their separation from food, or render them inactive in food and feed products (Jouany, 2007). Decades of research have introduced several strategies in removing or inactivating AFs in products, including physical (Herzallah, Alshawabkeh, & Fataftah, 2008;Sun et al, 2016) and chemical treatments (Méndez-Albores, Del Río-García, & Moreno-Martinez, 2007;Xiong, Hj, & Lt, 2012) as well as biological decontamination through microorganisms or enzymes (Adebo, Njobeh, Gbashi, Nwinyi, & Mavumengwana, 2015;Fruhauf, Schwartz, Ottner, Krska, & Vekiru, 2012;Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…JFDS-2017-0976 Submitted 6/16/2017, Accepted 2/7/2018 Owing to the harmful impact of AFs on human health, it is necessary to prevent the formation of AFs, ensure their separation from food, or render them inactive in food and feed products (Jouany, 2007). Decades of research have introduced several strategies in removing or inactivating AFs in products, including physical (Herzallah, Alshawabkeh, & Fataftah, 2008;Sun et al, 2016) and chemical treatments (Méndez-Albores, Del Río-García, & Moreno-Martinez, 2007;Xiong, Hj, & Lt, 2012) as well as biological decontamination through microorganisms or enzymes (Adebo, Njobeh, Gbashi, Nwinyi, & Mavumengwana, 2015;Fruhauf, Schwartz, Ottner, Krska, & Vekiru, 2012;Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Methods involving the use of fungi that secrete non-selective, ligninolytic enzymes are among the most promising biological decontamination strategies studied thus far (Kim et al 2017). Motomura et al (2003) isolated an unidentified enzyme from Pleurotus ostreatus that reduced the fluorescence of AFB 1 and attributed this to the disruption of its lactone ring that plays an important role in carcinogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that several viable or heat-killed Lactobacillus species can efficiently bind AFM1 (Assaf et al 2018a). It is noteworthy to mention that different cell wall components such as polysaccharides and peptidoglycans were thought to be involved in mycotoxins binding (Shetty and Jespersen 2006;Kim et al 2017). Hydrogen bonds and Van der Waals interactions were previously reported to be implicated in this binding (Shetty and Jespersen 2006;Yiannikouris et al 2006).…”
Section: Introductionmentioning
confidence: 97%